Pleasant Driving on Roads Maintained with Dowflake - Dow Chemical Company (1927)
Advertisement for Dowflake Calcium Chloride, a product of the Dow Chemical Company marketed for use to control dust on unpaved roads and parking lots, as well as a roadway deicer. The advertisement details the nuisance of dust arising from the use of motor cars on unpaved roads and extols the benefits of using Dowflake as a surface treatment to lock in moisture and reduce the maintenance and upkeep required of unpaved roads and drives. This advertisement appeared on page 95 of the May 7, 1927 edition of The Literary Digest .
Keywords: Chemical industry; Dow Chemical Company; Corporations; Advertising; Dust control; Roads--Maintenance and repair; Calcium chloride